The relationship between steeplechase hurdle economy, mechanics, and performance - Sarah Earl; Iain Hunter; Gary W. Mack; Matthew Seeley (Elsevier, 2015)
Background: Research surrounding the steeplechase is scarce, with most research focusing primarily on how biomechanical factors relate to maintaining running speed while crossing barriers. One area that has not been well explored is the relationship between biomechanical factors and hurdling economy. The purpose of this study was to investigate how performance times and biomechanical variables relate to hurdling economy during the steeplechase. Methods: This was accomplished by measuring running economy of collegiate and professional steeplechasers while running with and without hurdles. Biomechanical measures of approach velocity, takeoff distance, clearance height, and lead knee extension while hurdling, as well as steeplechase performance times were correlated to a ratio of running economy with and without hurdles. Results: While oxygen uptake was 2.6% greater for the laps requiring five barriers, there was no correlation between steeplechase performance time and the ratio of running economy during the hurdle and non-hurdle laps. Results also indicated no correlation between the aforementioned biomechanical variables and ratio of running economy during the hurdle and non-hurdle laps. Conclusion: Increasing approach velocity did not negatively affect running economy. Increased approach velocity is a benefit for maintenance of race pace, but does not hurt economy of movement.